Map of Da’wah: Religious Polarization and Affirmation of Identity of Islamic Societies In Lombok, Indonesia - Fahrurrozi, Fahrurrozi; Thohri, Muhammad (SANGKéP: Jurnal Kajian Sosial Keagamaan, 2020)
This study’s finding is religious polarization confirming the Identity of Lombok Islamic Societies emerging since before Indonesia’s independence by taking the religious movement form. Mainstream religious movement in Lombok is Sunni one and not all of them are under organizational flag, but generally based on educational institution. Minority non-sunni movement brought an effect and wahabi movement pattern emphasizing on “the differentiation” of religious practice, so that it is not ideological wrestling but identity contestation that occurs. Then, religiosity identity of Lombok Islamic societies is material-symbolic and accommodative in nature. The accommodative religious practice occurs in tasawwuf practices and encounters acculturation as the identity of Lombok Muslim. Islamic religious Identity in Lombok Sunni has been existing long before the development of religious organization and educational institution, so that the Sasak Islamic Identity encountered acculturation as the result of natural constructi on of Lombok Islamic societies. Organizational diversity, movement, and identity solidification can be a wealth as long as it is not debated in the public space